Precondition for ethnical cutural changes in Eastern Lithuana during Second world war and after the war - Anušauskas, Arvydas (Genocidas ir rezistencija, 2003)
The Second World War and ensuing changes in national borders left thousands of people either stateless or outside their state’s borders. This happened first and foremost to the people of Lithuania and Poland. Occupations and territorial partitions were the main causes of the ethnic changes that followed. The major national–cultural changes in eastern Lithuania in the second half of the 20th century were caused by enormous population losses, migration flows and the russification policy: the number of Lithuanian cultural islets decreased, the russification and sovietisation policy had a significant impact on the mentality of Vilnius region population, with some traditional values, mainly those related to Catholicism, maintained.
Keywords: Second World War; Eastern Lithuania; ethnical relationship; russification; migration